Use of Extracorporeal Membrane Oxygenation After Congenital Heart Disease Repair: A Systematic Review and Meta-Analysis - Wu, Yuhao; Zhao, Tianxin; Li, Yonggang; Wu, Shengde; Wu, Chun; Wei, Guanghui (Frontiers in Cardiovascular Medicine, 2020)
Introduction Extracorporeal membrane oxygenation (ECMO) has been widely used to treat cardiopulmonary failure in patients with congenital heart defects (CHD) postoperatively. A meta-analysis is performed for outcomes of postoperative CHD patients on ECMO. Methods Electronic databases, including PubMed, EMbase, and Cochrane Library CENTRAL were searched systematically from January 1990 to June 2020 for literature which reported the outcomes of postoperative CHD cases on ECMO. The scope of this search was restricted to articles published in English. Results Forty-three studies were included in this study, involving 3,585 subjects. Postoperative ventricular failure with low cardiac output was the most common indication of ECMO initiation. The pooled estimated incidence of in-hospital mortality was 56.8% (95% CI, 52.5% to 61.0%). Bleeding was the most common complication with ECMO with an incidence of 47.1% (95% CI, 38.5% to 55.8%). Multivariate meta-regression analysis revealed that single ventricular physiology (Coefficient 0.213, 95% CI 0.099 to 0.327, P=0.001) and renal failure (Coefficient 0.315, 95% CI 0.091 to 0.540, P=0.008) were two independent risk factors for in-hospital mortality.Conclusions There is an overall high in-hospital mortality of 56.8% in postoperative CHD patients on ECMO. Bleeding is the most common complication during ECMO running with an incidence of 47.1%. Single ventricular physiology and renal failure, as two independent risk factors, may potentially increase in-hospital mortality. Further studies exploring the differences in outcomes between ECMO and other extracorporeal life support strategies are warranted.